Spectral Reflectance in the Spatial-temporal Dynamic of Turbidity, Itaipu Reservoir, Brazil - Facco, Douglas Stefanello; Guasselli, Laurindo Antonio; Ruiz, Luis Fernando Chimelo; Simioni, João Paulo Delapasse; Dick, Daiane Gerhardt (Anuário do Instituto de Geociências, 2021)
Water quality and the useful life of reservoirs and dams are influenced by the entry of suspended solids, in addition to reducing their transparency and storage capacity. It is primary to monitor and analyses its space-time dynamics. Thus, the objective of this work is to characterize the dynamics of the Itaipu Reservoir waters from turbidity, rainfall and spectral reflectance data. To characterize the dynamics, the reservoir was divided into 18 aquatic compartments between upstream and downstream, using precipitation data from the TRMM sensor and Landsat 8 images in different precipitation situations. NDWI, MNDWI and NDTI water spectral indexes were calculated from Landsat 8 images. The results showed high correlation between the NDTI index and the turbidity (R² = 0.91). Then the NDTI images were reclassified into low, medium and high turbidity. A strong correlation between turbidity and 4 Band corresponding to the spectral range of red (R² = 0.94) was also obtained. The precipitation has a determinant influence, being the Paraná River, in the periods of greater precipitation, the main agent in sediment transport. The space-time dynamics showed that the lateral compartments of the reservoir have less influence on sediment transport. In this sense, our analysis brought new elements to understand the turbidity variation in these Itaipu Reservoir compartments, as well as the spectral reflectance dynamics in the space-time characterization related to turbidity.